2021
DOI: 10.3390/ijgi10110725
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Prediction Accuracy of Geomorphon-Based Automated Landform Classification: An Example from the Ionian Coastal Belt of Southern Italy

Abstract: Automatic procedures for landform extraction is a growing research field but extensive quantitative studies of the prediction accuracy of Automatic Landform Classification (ACL) based on a direct comparison with geomorphological maps are rather limited. In this work, we test the accuracy of an algorithm of automatic landform classification on a large sector of the Ionian coast of the southern Italian belt through a quantitative comparison with a detailed geomorphological map. Automatic landform classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…On a totally different account, in the last decades, the field of geomorphometry particularly focused on the study of automated or unsupervised classification of landforms, which can be suitable for a fast growth and analysis on larger areas (Gioia et al, 2021). Methods of this type only require a DEM but, since the translation from continuous morphometric variables to their derivatives is subordinated to scale‐dependence, many quantitative and automated approaches have been proposed (Drăguţ et al, 2011; Drăguţ & Eisank, 2011; Evans, 2003; Liucci et al, 2017; Liucci & Melelli, 2017), using secondary topographic attributes (Shary et al, 2005; Wilson & Gallant, 2000), the MRS method (Baatz & Schäpe, 2000), or using ALCoM statistical technique (Van Niekerk, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On a totally different account, in the last decades, the field of geomorphometry particularly focused on the study of automated or unsupervised classification of landforms, which can be suitable for a fast growth and analysis on larger areas (Gioia et al, 2021). Methods of this type only require a DEM but, since the translation from continuous morphometric variables to their derivatives is subordinated to scale‐dependence, many quantitative and automated approaches have been proposed (Drăguţ et al, 2011; Drăguţ & Eisank, 2011; Evans, 2003; Liucci et al, 2017; Liucci & Melelli, 2017), using secondary topographic attributes (Shary et al, 2005; Wilson & Gallant, 2000), the MRS method (Baatz & Schäpe, 2000), or using ALCoM statistical technique (Van Niekerk, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The tool is easy to use, and can detect up to ten possible landform geometries, classified either as flat, summit, ridge, shoulder, spur, slope, hollow, footslope, valley and depression. As highlighted by Gioia et al (2021) this tool uses 'a computer vision approach' that self-adapts to the topographic characteristic of the area.…”
Section: Slope (Sp)mentioning
confidence: 99%
“…In the form of input to a physically based hydrological model, geomorphons were successfully represented in the spatially distributed hydrological parameters of the upper reaches of a montane watershed in Brazil [33]. Yan et al (2020) found geomorphons to be optimal in the characterization of subaqueous riverbed features on the Yangtze River, China [35]; while the work of Gioia et al (2021) showed geomorphon-based classification to be a robust tool for the identification of geomorphological landscape elements at a large scale in southern Italy [37].…”
Section: Core Of Cranberry Gladesmentioning
confidence: 99%
“…However, these images are not sufficient to reflect topographic characteristics, which is significant for landform research. Digital elevation models (DEMs) are a significant type of remote sensing data and record elevation and terrain relief information [40][41][42][43]. In the field of geomorphology, DEMs have supported in-depth studies on the Earth's surface, including surface characterization [25,44], local terrain segmentation [45][46][47] and global landform classification [48,49].…”
Section: Introductionmentioning
confidence: 99%